KONSEP KEUTAMAAN AKHLAK VERSI AL-GHAZALI - Kasron Nst (Hijri, 2017)
Moral is a characteristic which is very important that must be had by all people, because the character is usual be used as a tool progression for humanity. The higher role of character is done, so more glorious that people have had it. Meanwhile the deferent of characteristics are between animal and human are the character and moral are showed in their daily activities. Human uphold the moral in this their live actually wished by Allah who had by everyone when the prophet Muhammad said. It is a purpose of Rasulullah Saw sent to this earth is to repair the moral people. Al-Ghazali said that to create an inner which supports the created the virtues of soul are called by Al-Ghazali happiness (Al-sa’adat Alhaqiqat). The virtues of moral has a lot of kinds, but it is called by Al-Ghazali is clarified